Lawn mower is used in gardens - YIN CHUANSONG (2018)
The utility model discloses a lawn mower is used in gardens, including frame, casing, cutter, fuel oil engine, drive assembly and push rod, the casing is installed in the frame, the cutter is locatedthe below of casing and rotates with the casing and be connected, fuel oil engine installs in the casing top, and it is connected with cutter realization transmission through drive assembly, install the throttle control switch on the push rod, front wheel and rear wheel are installed to both sides in the frame, grass collection box is installed to the rear side of casing, the opening that has on the lateral wall of casing and store the intercommunication, the axle sleeve is installed respectively on both sides about the rear side of frame, and the adjustable shelf is equipped with the dwang between two axle sleeves, the front end of dwang has the gag lever post, top an organic whole of grass collection box's front end is provided with the stopper, dwang and frame are through extension spring fixed connection. The